ECONOMIC EVALUATION OF THE TOLERANCE OF BEAN VARIETIES TO LEAFHOPPERS. Empoasca kraemeri ROSS & MOORE (HOMOPTERA CICADELLIDAE) - CARDONA, CESAR; CORTÉS, MARIA LUISA (Revista Colombiana de Entomología, 1991)
A series of nine field experiments were conducted at CIAT(Palmira, Valle del Cauca, Colombia,24°C, 80%1-1.9.) in order to measure the tolerance of bean (Phaseolus vulgaris L) varieties to the leafhopper, Empoasca kraemeri Ross & Moore. Eight bean lines improved for tolerance to the insect (ceded EMP), a tolerant check (Pijao), a susceptible check (BAT 41), and one of the parents used in the breeding process (BAT 1366) were laid out in a strip-plot design with three replications. Each of the varieties was exposed to different dosages of the insecticide monocrotophos in order to obtain a gradient infestation. Once the gradient of infestation was obtained, regressions were performed between levels of infestation and yields. Yield potential, loss function, and economic threshold were calculated for each variety. it was found that it was possible to reduce loss functions from 10 to 5 kg-nymph and to increase economic thresholds from 3 nymphs/leaf in EMP 187, the most tolerant variety. Economic analyses demonstrated the advantages of using leafhopper-tolerant varieties.